Ruddlesden–Popper 2D perovskites of type (C6H9C2H4NH3)2(CH3NH3)n−1PbnI3n+1 (n = 1–4) for optoelectronic applications - Rahil, Mohammad; Ansari, Rashid Malik; Prakash, Chandra; Islam, S. S.; Dixit, Ambesh; Ahmad, Shahab (Scientific reports, 2022)
Ruddlesden–Popper (RP) phase metal halide organo perovskites are being extensively studied due to their quasi-two dimensional (2D) nature which makes them an excellent material for several optoelectronic device applications such as solar cells, photo-detectors, light emitting diodes (LEDs), lasers etc. While most of reports show use of linear carbon chain based organic moiety, such as n-Butylamine, as organic spacer in RP perovskite crystal structure, here we report a new series of quasi 2D perovskites with a ring type cyclic carbon group as organic spacer forming RP perovskite of type (CH) 2 (MA) n−1 Pb n I 3n+1 ; CH = 2-(1-Cyclohexenyl)ethylamine; MA = Methylamine). This work highlights the synthesis, structural, thermal, optical and optoelectronic characterizations for the new RP perovskite series n = 1–4. The demonstrated RP perovskite of type for n = 1–4 have shown formation of highly crystalline thin films with alternate stacking of organic and inorganic layers, where the order of PbI 6 octahedron layering are controlled by n-value, and shown uniform direct bandgap tunable from 2.51 eV (n = 1) to 1.92 eV (n = 4). The PL lifetime measurements supported the fact that lifetime of charge carriers increase with n-value of RP perovskites [154 ps (n = 1) to 336 ps (n = 4)]. Thermogravimetric analysis (TGA) showed highly stable nature of reported RP perovskites with linear increase in phase transition temperatures from 257 °C (n = 1) to 270 °C (n = 4). Scanning electron microscopy (SEM) and energy dispersive X-ray analysis (EDAX) are used to investigate the surface morphology and elemental compositions of thin films. In addition, the photodetectors fabricated for the series using (CH) 2 (MA) n−1 Pb n I 3n+1 RP perovskite as active absorbing layer and without any charge transport layers, shown sharp photocurrent response from 17 nA/cm 2 for n = 1 to 70 nA/cm 2 for n = 4, under zero bias and low power illumination conditions (470 nm LED, 1.5 mW/cm 2 ). Furthermore, for lowest bandgap RP perovskite n = 4, (CH) 2 MA 3 Pb 4 I 13 the photodetector showed maximum photocurrent density of ~ 508 nA/cm 2 at 3 V under similar illumination condition, thus giving fairly large responsivity (46.65 mA/W). Our investigations show that 2-(1-Cyclohexenyl)ethylamine based RP perovskites can be potential solution processed semiconducting materials for optoelectronic applications such as photo-detectors, solar cells, LEDs, photobatteries etc.